Gut Virome and Inflammatory Bowel Disease. Issue 7 (July 2016) - Lopetuso, Loris R.; Ianiro, Gianluca; Scaldaferri, Franco; Cammarota, Giovanni; Gasbarrini, Antonio
Abstract : Abstract: Gut virome has been shown to yield some beneficial effects on humans, being deeply involved in physiology, inflammation, immunity, and disease. Together with transkingdom interactions, it can interplay with genetic variation in the host to establish specific phenotypes. These interactions can lead to phenotypes not observed with either the virus or the host variation alone. Unfavorable alteration of gut virome composition has been implicated in chronic, and perhaps also systemic, immune disorders, such as in the pathogenesis of inflammatory bowel disease. This review focuses on what is currently known regarding the role of commensal gut virome in chronic gut inflammation, and speculate on the important translational implications in regard to gut virome modulation in inflammatory bowel disease with the end goal of promoting gut health. Abstract : Article first published online 20 May 2016.